2013
DOI: 10.1063/1.4813630
|View full text |Cite
|
Sign up to set email alerts
|

A ray tracing study of shock leakage in a model supersonic jet

Abstract: Recent work has described screech noise from a supersonic jet as being due to leakage of a wave that is otherwise trapped in the jet's interior. In that work, the simplest of many techniques used is ray tracing for a single shear-layer modeled as a row of Stuart vortices. In the present work, a lower row of vortices is added to form a plane jet. Instead of plotting ray paths, a technique of visualization analogous to streaklines is used that better corresponds to instantaneous density fields as observed, for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…They observed that the passage of an eddy at a shock position may cause the shock to leak out from the mixing layer. Shariff & Manning (2013) observed the same phenomenon from a ray tracing study. Shock leakage has also been recognised as being the screech acoustic feedback generation mechanism by Berland, Bogey & Bailly (2007) by means of a large-eddy simulation of a planar jet.…”
Section: Introductionsupporting
confidence: 58%
“…They observed that the passage of an eddy at a shock position may cause the shock to leak out from the mixing layer. Shariff & Manning (2013) observed the same phenomenon from a ray tracing study. Shock leakage has also been recognised as being the screech acoustic feedback generation mechanism by Berland, Bogey & Bailly (2007) by means of a large-eddy simulation of a planar jet.…”
Section: Introductionsupporting
confidence: 58%
“…A second criterion to select the feedback source is to account only for those located at a shock tip. This is the most probable location according to numerical studies of shock leakage by Suzuki et al, 8 Shariff and Manning, 9 or Berland et al 10 It is shown that a moving shock is a source of compression and expansion waves that are normally internally reflected, but that can leak if some requirements on the vorticity in the shear layer are met, especially for large vortical structures, thus if coherent structures are developed enough. This analysis will assume the speed of sound constant while traveling in the jet vicinity, and there is no account for non-linear effects.…”
Section: Introductionmentioning
confidence: 97%
“…Shock-containing free shear flows frequently exhibit some form of aeroacoustic resonance, the most well known of these resonant processes are those that produce screech or impingement tones. 1 These resonance processes can be divided into four discrete processes: a downstream-propagating wave, 2-4 a tonal generation mechanism, [5][6][7][8][9] an upstream-propagating wave, [10][11][12][13][14][15] and a receptivity mechanism. [16][17][18] Of these, the downstream-propagating wave is the only process where energy is provided to the resonance loop; 2 the growth of the instability wave is driven by the extraction of energy from the mean flow.…”
Section: Introductionmentioning
confidence: 99%